Simulating Effects of Variable Stoichiometry and Temperature on Mixotrophy in the Harmful Dinoflagellate Karlodinium veneficum - Lin, Chih-Hsien; Flynn, Kevin J.; Mitra, Aditee; Glibert, Patricia M. (Frontiers in Marine Science, 2018)
Results from a dynamic mathematical model are presented simulating the growth of the harmful algal bloom (HAB) mixotrophic dinoflagellate Karlodinium veneficum and its algal prey, Rhodomonas salina. The model describes carbon-nitrogen-phosphorus-based interactions within the mixotroph, interlinking autotrophic and phagotrophic nutrition. The model was tuned to experimental data from these species grown under autotrophic conditions and in mixed batch cultures in which nitrogen:phosphorus stoichiometry (input molar N:P of 4, 16, and 32) of both predator and prey varied. A good fit was attained to all experimentally derived carbon biomass data. The potential effects of temperature and nutrient changes on promoting growth of prey and thus K. veneficum bloom formation were explored using this simulation platform. The simulated biomass of K. veneficum was highest when they were functioning as mixotrophs and when they consumed prey under elevated N:P conditions. The scenarios under low N:P responded differently, with simulations showing larger deviation between mixotrophic and autotrophic growth, depending on temperature. When inorganic nutrients were in balanced proportions, lower biomass of the mixotroph was attained at all temperatures in the simulations, suggesting that natural systems might be more resilient against Karlodinium HAB development in warming conditions if nutrients were available in balanced proportions. These simulations underscore the need for models of HAB dynamics to include consideration of prey; modeling HAB as autotrophs is insufficient. The simulations also imply that warmer, wetter springs that may bring more N with lower N:P, such as predicted under climate change scenarios for Chesapeake Bay, may be more conducive to development of these HABs. Prey availability may also increase with temperature due to differential growth temperature responses of K. veneficum and its prey.